2019
DOI: 10.4103/ijpsym.ijpsym_441_18
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Attitudes toward Sexual Health and Common Sexual Practices among College Students - A Survey from Vellore, Tamil Nadu, India

Abstract: Background: Indian society is considered to have conservative attitudes regarding sex and is ambivalent about the concept of sex education. Previous reports suggest that a considerable proportion of Indian youth have inadequate sexual knowledge and hold a variety of sexual misconceptions. Methodological flaws limit the generalizability of some earlier studies. Aims: This study assessed knowledge and attitude toward sexual health and common sexual practices among college… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…41 The influence of social and cultural issues and misconceptions about sexual functions cannot be denied and requires more research. 27,28,[42][43][44] However, the findings of the study indicate that exploration of comorbidities and targeting them during treatment in addition to accepted methods may increase the outcome of treatment of FSD.…”
Section: Discussionmentioning
confidence: 94%
“…41 The influence of social and cultural issues and misconceptions about sexual functions cannot be denied and requires more research. 27,28,[42][43][44] However, the findings of the study indicate that exploration of comorbidities and targeting them during treatment in addition to accepted methods may increase the outcome of treatment of FSD.…”
Section: Discussionmentioning
confidence: 94%
“… 30 Previous research involving Indian and Turkish participants claimed that individuals who are more conservative are more likely to be negative toward masturbation and premarital sexual behaviors. 31 , 32 Previous studies have also shown that teens with conservative sexual attitudes are less likely to engage in premarital sex. The current study also found that adolescents with conservative sexual beliefs regarding masturbation were less likely to engage in premarital sex.…”
Section: Discussionmentioning
confidence: 99%
“…11 Currently, the Indian community is considered to have conservative attitudes toward sex. 12 A study reported, decrease of sexual excitement after first years of marriage, due to the birth of children, and the stress of life and family problems, older age group reported having sexual intercourse as an essential activity rather than personal interest. 13 When studying sexual behavior among married women in North India, Avasthi et al 14 reported similar findings of that of Khan et al 9 in Bangladesh.…”
Section: Discussionmentioning
confidence: 99%